2008
DOI: 10.1111/j.1440-1819.2008.01754.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognition in first‐degree healthy relatives (siblings) of bipolar affective disorder patients

Abstract: Aim:Cognitive deficits have been presupposed to be endophenotypic markers in bipolar disorder, but few studies have ascertained the cognitive deficits in healthy relatives of bipolar disorder patients. The aim of the present study was to assess the cognitive functions of first-degree relatives of patients with bipolar disorder and compare them with healthy controls.Methods: Ten first-degree apparently healthy relatives of patients with bipolar disorder were compared with 10 age-and education-matched control su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…Although current literature does not view such biases as primary endophenotypic markers of BD, both healthy pediatric BD offspring (Gotlib et al 2005) and adult siblings of BD patients exhibit affective processing biases toward negative stimuli in tasks of impulse control (Clark et al 2005;Klimes-Dougan et al 2006;Maziade et al 2009;Brand et al 2012). Similar to patients with BD, at-risk individuals display deficits in sustained attention and executive functioning (Zalla et al 2004;Frangou et al 2005;Klimes-Dougan et al 2006;Trivedi et al 2008;Kulkarni et al 2010;Diwadkar et al 2011) which suggests that cognitive deficits and affective processing biases could be interrelated, and may constitute markers of vulnerability to BD.…”
Section: Introductionmentioning
confidence: 99%
“…Although current literature does not view such biases as primary endophenotypic markers of BD, both healthy pediatric BD offspring (Gotlib et al 2005) and adult siblings of BD patients exhibit affective processing biases toward negative stimuli in tasks of impulse control (Clark et al 2005;Klimes-Dougan et al 2006;Maziade et al 2009;Brand et al 2012). Similar to patients with BD, at-risk individuals display deficits in sustained attention and executive functioning (Zalla et al 2004;Frangou et al 2005;Klimes-Dougan et al 2006;Trivedi et al 2008;Kulkarni et al 2010;Diwadkar et al 2011) which suggests that cognitive deficits and affective processing biases could be interrelated, and may constitute markers of vulnerability to BD.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported impaired response inhibition in healthy relatives of patients with bipolar disorder [11][12][13][14], whereas other studies reported intact response inhibition [15][16][17][18]. Moreover, most of the studies reported intact set shifting and cognitive flexibility [11,14,15,[19][20][21][22], and some studies reported impairments in those abilities [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The healthy relatives were mostly selected from mixed relative groups (include not only unaffected parents but also patients' offspring and siblings) [11,[13][14][15][16][17][18]22,23,25,26], and the majority of the studies involved siblings [12,[18][19][20]24,27] or even offspring [21]. Studying parents rather than siblings decreases common environmental factors, which are more present among siblings and may be confused with heredity.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding cognitive abnormalities in bipolar disorder and schizophrenia can inform our understanding of the neurobiological systems that are disrupted by these disorders as well as provide a link between neurobiology and observed symptoms and behaviors (Joseph, Frazier, Youngstrom, & Soares, 2008). This information may also enhance our understanding of the course of both illnesses (Antila et al, 2007;Christensen, Kyvik, & Kessing, 2006;Trivedi et al, 2008). Perhaps most important, knowledge regarding specific cognitive deficits can be used to tailor cognitive remediation strategies and goals.…”
mentioning
confidence: 99%